A reflection of the global history: the Persian Empire’s role in the relations between the Roman Empire and China (1st-7th century CE) - Li, Qiang (Επιστημονική Επετηρίδα Παιδαγωγικού Τμήματος Νηπιαγωγών Πανεπιστημίου Ιωαννίνων, 2016)
The Roman Empire and China had close relations through the famous Silk Road in history. However, there existed only indirect relations for the obstacles of the intermediaries. The Persian Empire had been always the main intermediary which affected the communications between the two empires for the first seven centuries in the Common Era. Based on different sources, mainly from Chinese side, analyzing the role of the Persian Empire in the relations between the Roman Empire and China will be helpful for understanding the interaction of the West and the East in global history, which likely sheds light on the modern international relations in the new century.